2015
DOI: 10.1071/sh14191
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and congenital syphilis in selected Latin America and Caribbean countries: a multi-country analysis using data from the Perinatal Information System

Abstract: This paper aims to describe epidemiological and programmatic characteristics related to maternal and congenital syphilis in selected countries of Latin America and Caribbean for the period 2010-12. Methods: The report is based on a multi-country, quantitative and qualitative analysis from data collected from several sources, representing a compilation of country reports from nine countries as part of the 2012 mid-term evaluation of the Strategy. Data was collected based on standardised procedures at country le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 2 publications
0
15
0
9
Order By: Relevance
“…We attempted to measure the association of SBRs and maternal syphilis prevalence . However, as reported syphilis prevalence is closely related to access to the screening test, the obtained results did not seem to be plausible. We also tried to collect data on the country‐level prevalence of congenital anomalies, to explore its relation to SBR, but data were only reported for nine countries in Latin America .…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to measure the association of SBRs and maternal syphilis prevalence . However, as reported syphilis prevalence is closely related to access to the screening test, the obtained results did not seem to be plausible. We also tried to collect data on the country‐level prevalence of congenital anomalies, to explore its relation to SBR, but data were only reported for nine countries in Latin America .…”
Section: Discussionmentioning
confidence: 99%
“…The main surveillance systems in Brazil are the Sistema de Informação de Agravos de Notificação–Sinan (Notifiable Diseases Information System) and the Sistema de Informação de Mortalidade –SIM (Mortality Information System). However, quality flaws in the registration of CS cases and deaths hinder a reliable analysis of the problem [5], a situation that is also identified in other countries of Latin American and Caribbean [6]. Therefore, despite the magnitude of the problem, morbidity and mortality rates from this disease remain underreported [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…In all, 29.2% of the 414 fetal and infant deaths found in this study referred to cases of mothers with syphilis reported to the Sinan. This finding shows that syphilis is probably not being diagnosed during prenatal care [26] or that diagnosed cases are not being reported. The elimination of CS is possible if diagnosis and treatment are instituted in a timely manner.…”
Section: Discussionmentioning
confidence: 99%